COMPARATIVE STUDY BETWEEN LEARNING OUTCOMES STUDENT USING MODEL EXPOSITORY AND COOPERATIVE LEARNING COURSE IN THE DEVELOPMENT OF LEARNERS - WAHYUNINGSIH, SETYA; FATIMAH TS, TETTY (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of this research was to determine the learning outcomes of students in lecturesdevelopment of learners learning outcomes of students in the subject of the development of learnerswith learning model cooperative learning research methods and the nature of the study in the firstphase begins the study of theoretical, primarily implemented in the literature, empirical studiesconducted when a test model of learning. Sample in this research is the education of students whotook the English language courses development of learners as many as 75 people. Data were collectedto measure the effectiveness of the use of models of student learning using a written test of 70multiple choice questions and one about the form of case studies. Result of the study is the use ofmodels Expository learning on the eye lecture development of learners. The result is more effectivethan the use of cooperative learning models.